2009
DOI: 10.1099/ijs.0.009779-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and taxonomy of a diverse collection of Bradyrhizobium strains based on multilocus sequence analysis of the 16S rRNA gene, ITS region and glnII, recA, atpD and dnaK genes

Abstract: Phylogeny and taxonomy of a diverse collection of Bradyrhizobium strains based on multilocus sequence analysis of the 16S rRNA gene, ITS region and glnII, recA, atpD and dnaK genes were obtained with MLSA of glnII, recA, atpD and dnaK. Greatest variability was observed when the atpD gene was amplified, and five strains related to B. elkanii revealed a level of variability never reported before. Another important observation was that a group composed of strains USDA 110, SEMIA 5080 and SEMIA 6059, all isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
114
3
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(145 citation statements)
references
References 82 publications
(84 reference statements)
18
114
3
5
Order By: Relevance
“…Although high percentages of 16S rRNA gene sequence similarity were obtained, previous reports have suggested that closely related species of the genus Bradyrhizobium are difficult to distinguish using 16S rRNA gene sequence analysis (Willems et al, 2001;Menna et al, 2009). Therefore, multi locus sequence analysis (MLSA) was performed with glnII (537 bp), recA (415 bp) and rpoB (429 bp) following previous reports (Vinuesa et al, 2005;Martens et al, 2008, Menna et al, 2009.…”
mentioning
confidence: 97%
“…Although high percentages of 16S rRNA gene sequence similarity were obtained, previous reports have suggested that closely related species of the genus Bradyrhizobium are difficult to distinguish using 16S rRNA gene sequence analysis (Willems et al, 2001;Menna et al, 2009). Therefore, multi locus sequence analysis (MLSA) was performed with glnII (537 bp), recA (415 bp) and rpoB (429 bp) following previous reports (Vinuesa et al, 2005;Martens et al, 2008, Menna et al, 2009.…”
mentioning
confidence: 97%
“…Highest similarity was observed with Bradyrhizobium huanghuaihaiense, followed by Bradyrhizobium arachidis (Table 2). Despite the 16S rRNA gene being broadly used in phylogenetic analyses, in some bacterial genera, such as Bradyrhizobium, the sequences are considered highly conserved, limiting species delineation Helene et al, 2015;Menna et al, 2009). However, it is noteworthy that this new group with the BR strains could be observed in the analysis of the 16 rRNA gene (Fig.…”
mentioning
confidence: 98%
“…The higher variability of the ITS region in comparison with the 16S rRNA gene among species of the genus Bradyrhizobium allows a better delineation of species (Germano et al, 2006;Menna et al, 2009). In the ITS phylogram, the BR strains were clustered in a clade distinct from other bradyrhizobia, with a bootstrap support of 100 %, and showed higher similarity with Bradyrhizobium japonicum (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations